Hematohidrosis in Pediatric Practice – a Case Report and Review of the Literature - Matsyura, Oksana; Besh, Lesya; Jefimova, Svitlana; Slivinska-Kurchak, Khrystyna; Gerasymov, Sergiy (Acta medica Lituanica, 2024)
Hematohidrosis (bloody sweat) is a symptom of trophic damage to the vascular wall, in which sweat mixes with blood and seeps onto undamaged areas of the skin in the form of red or pink liquid (depending on the ratio of sweat to blood).  In our study we have analyzed 25 case reports of hematohidrosis in children, reported throughout the world using PubMed, ResearchGate with detailed description and opened access. We took into consideration: age of the patient, sex, location of bloody excretion, cause or trigger, treatment and its effectiveness.Our clinical case present a 9-year-old girl complained of a periodic bleeding from the intact skin of the face, neck, thighs (without visible damage to the skin) manifested by red or pink liquid, nosebleeds, and bloody discharge from the mucous membrane of the eyes. The secretions were of varying intensity and lasted up to several hours. Most of all episodes are associated with a strong emotional exertion. One of the theories of hematohidrosis pathogenesis is evident vasoconstriction of the blood vessels surrounding the sweat glands, provoked by hyperactivation of the sympathetic nervous system, which is followed by their excessive vasodilation up to rupture and blood entering the sweat gland ducts. Capillary endothelial cells are known to contain β2-adrenoceptors, which, through the modulation of nitric oxide release, cause endothelium-dependent vasodilation. Blocking β-adrenoceptors (for example, propranolol) prevents excessive vasodilation of blood vessels and, accordingly, their rupture and blood flow to the sweat gland.We managed to find out that the patient’s bloody sweat was a manifestation of a separate pathological phenomenon, and not one of the symptoms of another disease. A properly formed treatment complex and the great trust of the parents enabled to stabilize the child’s condition, and later to cure her. Currently, hematohidrosis is recognized as an independent disease that requires in-depth study of the triggering mechanisms of development, pathogenetic and clinical features.
Keywords: hematidrosis; case; child; diagnosis; treatment